Perspektif Paradigma Naratif dalam Aktivitas Mendongeng untuk Menanamkan Nilai Moral Anak Usia Dini: Studi Kasus pada Komunitas Kampung Dongeng Kito Bengkulu - Dwi Hari Andayani, Dwi Hari Andayani; Lisa Adhrianti, Lisa Adhrianti; Alfarabi, Alfarabi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication is a basic human activity, both as individuals and as groups. Fairy tales and factual stories are closely related to the formation of character, not only individual human character but human character in a nation, in storytelling activities it is closely related to the delivery of messages between the storyteller or communicator and his listeners or also called communicants, hence the delivery of narratives. The right way to tell a story has a big influence on the message that is created and the moral values that the storyteller wants to convey.